2016
DOI: 10.1088/1361-6498/37/1/84
|View full text |Cite
|
Sign up to set email alerts
|

Practical experiences in the transfer of clinical protocols between CT scanners with different ATCM systems

Abstract: Automatic tube current modulation (ATCM) systems to aid in optimizing dose and image noise have become standard on computed tomography (CT) scanners over the last decade. ATCM systems of the main vendors modulate tube current in slightly different ways, with some using a control parameter related to image noise (e.g. Toshiba, GE) while others use a quality reference image mAs (e.g. Siemens). The translation of clinical protocols including ATCM operation between CT scanners from different manufacturers in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Applying the technique of automatic tube current adjustment, appropriately increase the tube current of iliac artery and appropriately decreasing the tube current of thigh and calf artery can ensure the noise consistency of the whole lower limb scanning range and reduce unnecessary radiation dose ( 22 24 ). The results of this study showed that there was no significant differences in CT, SD, SNR, and CNR values of femoral artery, popliteal artery and posterior tibial artery between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Applying the technique of automatic tube current adjustment, appropriately increase the tube current of iliac artery and appropriately decreasing the tube current of thigh and calf artery can ensure the noise consistency of the whole lower limb scanning range and reduce unnecessary radiation dose ( 22 24 ). The results of this study showed that there was no significant differences in CT, SD, SNR, and CNR values of femoral artery, popliteal artery and posterior tibial artery between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity analysis excluding vertebrae with incident density abnormalities and artefacts added robustness to the assessment of true changes in trabecular bone density. On the other hand, the sensitivity analysis stratified by centres from different countries (Leiden, Netherlands and Herne, Germany) added to the external validity of the results, limiting the concerns regarding HU values obtained from distinct automatic exposure control implementation and iterative reconstruction algorithms [18,39]. Moreover, the results coming from different CT scanners in different centres (Canon in Leiden, and Siemens in Herne), likely represent the most feasible approach for HU measurements in future studies (especially if multicentric).…”
Section: Discussionmentioning
confidence: 99%
“…From a previous study on transferring of CT protocols for CT ATCM system, the protocols for both scanners were matched for noise in patients who had cross-sectional areas that approximated to that of the trunk for a large adult Thai patient. [ 10 ] The minimum mAs for the GE scanner was set at 80 mAs to restrict modulation that can affect image quality for small patients, and this resulted in the mAs remaining constant throughout scans for some patients, so data for these individuals were excluded from the study. There is no option for users to select the mAs range for the Siemens scanner, because of the mode of operation, as described above.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%